Prognostic value of the platelet-to-lymphocyte ratio in lung cancer patients receiving immunotherapy: A systematic review and meta-analysis - Wang, Haoyu; Li, Cui; Yang, Ruiyuan; Jin, Jing; Liu, Dan; Li, Weimin (PloS one, 2022)
Current studies have revealed that the platelet to lymphocyte ratio (PLR) may lead to a poor prognosis in lung cancer patients receiving immunotherapy. We conducted a meta-analysis to explore the prognostic value of PLR in lung cancer patients receiving immunotherapy. We retrieved potential studies from the PubMed, Web of Science, Embase, and Scopus databases up to June 2021 and merged the hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) to evaluate the association between PLR and overall survival (OS) or progression-free survival. Fourteen studies involving 1761 patients were included in our meta-analysis. The results indicated that an elevated level of pretreatment PLR was associated with poorer OS and PFS in lung cancer patients receiving immunotherapy (OS: HR = 1.88, 95% CI: 1.37-2.58; PFS: HR = HR = 1.40, 95% CI: 1.11-1.76). The association remained consistent after subgroup analysis and was robust even after sensitivity analysis. PLR may be a prognostic factor of lung cancer patients receiving immunotherapy, which can lead to worse survival outcomes. However, further studies are necessary for evidence in clinical application.